PENGARUH KUALITAS PELAYANAN, FASILITAS DAN KELENGKAPAN PRODUK TERHADAP KEPUASAN KONSUMEN PADA AHASS SHINTA MOTOR BANJARNEGARA - Lustono, Lustono (Medikonis, 2022)
This research takes the title "The Effect of Service Quality, Facilities and Product Completeness on Consumer Satisfaction at AHASS Shinta Motor Banjarnegara". This study aims to determine the effect of service quality, facilities and product completeness on consumer satisfaction at AHASS Shinta Motor Banjarnegara. This study uses quantitative methods, using primary data from consumers of AHASS Shinta Motor Banjarnegara as many as 10,435 people. While the sample in this study were 100 respondents. Data analysis used classical assumption test, namely normality test, heteroscedasticity test, multicoloniarity test, for hypothesis testing using t test and F test. Data analysis tool using SPSS. The results of this study by partial test indicate that service quality has an effect and is significant on consumer satisfaction, facilities have no and no significant effect on customer satisfaction, product completeness has no effect and is not significant on consumer satisfaction. Simultaneous test results show that the quality of service, facilities and product completeness simultaneously and significantly affect customer satisfaction. The value of the coefficient of determination in this study is 0.616. This shows the ability of the independent variable to explain the dependent variable by 61.6% while the rest is explained by other variables not included in this study.